A Postural Risk Assessment of Steamer Production Workers Using RULA and REBA - Darmawan, Vertic Eridani Budi; Indra, Sofiandi Dwi; Larasati, Aisyah; Nugraha, Cahya; Fathullah, Muhammad (Universitas Atma Jaya Yogyakarta, 2024)
The present study examined the work posture of the worker as a basis for correcting bad postures in the workplace. Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) methods are applied to evaluate the postural risk assessment which is related to musculoskeletal disorders (MSDs). There are five workers at UD. Sidoarjo National Ship is chosen to analyze the risk posture for this study. Based on observations and calculations at UD. Sidorajo National Ship, it was found that workers were still using less than optimal methods or not supported by ergonomic workstations. The study reveals that every worker in UD. Sidoarjo National Ship workstations have a risk of getting MSDs. These indicated that the worker’s work posture was less ergonomic and required changes to lessen the risk of MDSs.